Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13034-020-00327-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in adolescents displaced by the armed conflict: findings from the Colombian national mental health survey

Abstract: Background: Colombia has one of the largest populations of internally displaced individuals by an armed conflict. However, there is no data demonstrating its effect on health, particularly in adolescents. Purpose: To describe the prevalence and associations of mental illness in the adolescent population displaced by violence in Colombia. Methods: We conducted a secondary analysis of the 2015 National Mental Health Survey (NMHS), which provides data of mental health issues (SRQ), mental health disorders (CIDI-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Among the studies using general samples, 15 [ 17 , 18 , 20 , 30 , 39 , 47 49 , 54 , 55 , 77 , 79 , 83 , 85 , 88 ] reported on the prevalence of suicide attempts ( Table 3 ). The results are ordered by timeframe for the prevalence estimates and then sub-grouped by population type.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies using general samples, 15 [ 17 , 18 , 20 , 30 , 39 , 47 49 , 54 , 55 , 77 , 79 , 83 , 85 , 88 ] reported on the prevalence of suicide attempts ( Table 3 ). The results are ordered by timeframe for the prevalence estimates and then sub-grouped by population type.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies in general samples compared the prevalence of suicide attempts in displaced people to the host population. Only five of these studies [ 20 , 30 , 54 , 77 , 81 ] reported data in formats that could be presented visually in forest plots ( Fig 3 ). Two of these studies were in refugees granted asylum, one was in mixed refugees & asylum seekers, one was in internally displaced people, and one was a pooled report of mixed refugee populations across 21 countries [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, psychosocial support and training in parenting patterns for caregivers who are survivors of armed conflict may provide one avenue. More addressing structural challenges that weaken families can help to reduce post-exposure symptoms and promote recovery among conflict-affected children (Betancourt et al , 2015; Cummings et al , 2016; El-Khodary et al , 2020; Hall et al , 2014; Marroquín Rivera et al , 2020; Panter-Brick et al , 2014; Sim et al , 2018; Tol et al , 2014; Taylor et al , 2016a). Better integration of mental healthcare into primary care may be an additional step that has the potential to address the wider systemic effects of armed conflict on mental health (Rodríguez de Bernal and Rubiano Soto, 2016).…”
Section: Discussionmentioning
confidence: 99%